2023
DOI: 10.1002/mbo3.1347
|View full text |Cite
|
Sign up to set email alerts
|

Temporal disturbance of a model stream ecosystem by high microbial diversity from treated wastewater

Abstract: Microbial communities in freshwater streams play an essential role in ecosystem functioning via biogeochemical cycling. Yet, the impacts of treated wastewater influx into stream ecosystems on microbial strain diversity remain mostly unexplored. Here, we coupled full‐length 16S ribosomal RNA gene Nanopore sequencing and strain‐resolved metagenomics to investigate the impact of treated wastewater on a mesocosm system (AquaFlow) run with restored river water. Over 10 days, community Bray–Curtis dissimilarities be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…This was accompanied with a uniform increase of diversity compared to all other mesocosm setups, including both controls and other stressor combinations (Shannon: p=0.0009, Simpson: p=0.008; Figure S2 ). Amplicon-based microbiome analysis is well known to be affected by primer-bias and PCR-bias which may lead to an unsuitable measure for accurate river bacteriome analyses (Stach et al, 2023). Microbiome analysis based on rpS3 gene sequences extracted from de novo assembled metagenomes aims at overcoming these issues by being PCR-free, and covering eukaryotic gene signatures and a higher diversity of uncultured prokaryotic microorganisms (Sharon et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was accompanied with a uniform increase of diversity compared to all other mesocosm setups, including both controls and other stressor combinations (Shannon: p=0.0009, Simpson: p=0.008; Figure S2 ). Amplicon-based microbiome analysis is well known to be affected by primer-bias and PCR-bias which may lead to an unsuitable measure for accurate river bacteriome analyses (Stach et al, 2023). Microbiome analysis based on rpS3 gene sequences extracted from de novo assembled metagenomes aims at overcoming these issues by being PCR-free, and covering eukaryotic gene signatures and a higher diversity of uncultured prokaryotic microorganisms (Sharon et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Binning contigs into MAGs followed the approach described in Stach et al, 2023. In brief, MetaBAT2 (Kang et al, 2019), ABAWACA (Brown et al, 2016), and MaxBin2 (Wu et al, 2016) were used as binning tools.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Compared to other sequencing techniques, Oxford Nanopore is much faster and delivers results within 2 h. 13 The procedure was already used for various targets in wastewater research such as the identification of epidemiological causes, pathogen variations, or correlations between antibiotic usage and AMR abundance. 14,18,19 The bottleneck of sequencing is the correct preparation of the sample as the results can vary widely depending on the used nucleic acid extraction method. 20−22 A recent report showed that the detection of bacterial DNA in wastewater can be influenced by the extraction procedure used.…”
mentioning
confidence: 99%
“…Compared to other sequencing techniques, Oxford Nanopore is much faster and delivers results within 2 h . The procedure was already used for various targets in wastewater research such as the identification of epidemiological causes, pathogen variations, or correlations between antibiotic usage and AMR abundance. ,, …”
mentioning
confidence: 99%